Hazardous Medications in Children with Egg, Red Meat, Gelatin, Fish, and Cow’s Milk Allergy - Caglayan-Sozmen, Sule (Medicina (Kaunas), 2019)
Childhood food allergies are a growing public health problem. Once the offending food allergens have been identified, a strict elimination diet is necessary in treatment or prevention of most of the allergic reactions. Accidental food ingestion can lead to severe anaphylaxis. Food- derived substances can be used in medications at various stages of the manufacturing process. In this review, the possible roles of medications which may contain egg, red meat, gelatin, and fish allergens on allergic reactions in children with food allergy were evaluated.